Attitudes and attitude change. [article]. - Bohner, Gerd
Attitudes and attitude change remain core topics of contemporary social psychology. This selective review emphasizes work published from 2005-2009. It addresses constructionist and stable-entity conceptualizations of attitude, the distinction between implicit and explicit measures of attitude, and implications of the foregoing for attitude change.-(from the author)
Keywords: Dickel, Nina; Attitude measurement; Embodied cognition; Explicit attitude; Implicit attitude; Meta-cognition.; Persuation